Jurnal Hukum Perlindungan Nasabah dalam Penggunaan Layanan Mobile Banking di Bank Syariah Kota Medan - Merry Roseline Pasaribu; Siti Roro Ayu Ningtias (CV Rewang Rencang, 2025)
This study aims to analyze customer protection strategies in mobile banking services at Islamic banks, focusing on the application of sharia principles, digital security, and compliance with national regulations. The phenomenon studied is the increasing use of mobile banking, which poses a risk of cyberattacks and data breaches. The approach used was a qualitative case study method at one national Islamic bank. Data were collected through in-depth interviews with five key informants consisting of bank officials, information security experts, and customers; observations of digital service processes; and analysis of internal documents and related regulations. Data analysis was conducted thematically to identify patterns and relationships between themes. The results show that customer protection encompasses four main pillars: (1) strengthening security through layered encryption and authentication, (2) digital customer literacy, (3) responsive complaint mechanisms, and (4) compliance with sharia values such as trustworthiness and justice. The implementation of these four pillars increases customer trust and reduces the risk of cybercrime. These findings contribute to the development of the concept of sharia-based consumer protection and offer policy recommendations for strengthening digital security in the banking industry.